SEMINAR PEMANFAATAN MICROSOFT POWERPOINT SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI SMP ISLAM GARDEN SCHOOL - Wardatul Gufronia; Muftiyah Zakiyah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
The advancement of information technology encourages the world of education to integrate more attractive and interactive learning media. One of the media that is widely used is Microsoft PowerPoint, which is no longer limited to presentation tools, but also as a teaching medium that supports learning effectiveness. This study aims to describe how Microsoft PowerPoint is used as an interactive learning medium at SMP Islam Garden School. The research method used is descriptive qualitative, with data collection techniques through direct observation, interviews, and documentation during the learning process. The results obtained show that PowerPoint, with the support of visual features such as animation, audio, and images, is able to increase students' interest in learning, active participation, and understanding of the material. In addition, PowerPoint encourages teachers to be more innovative in compiling learning materials, and provides space for students to convey their ideas creatively. Overall, PowerPoint has proven to be an effective, easy-to-use, and relevant learning medium in supporting the quality of education in the digital era.